Beneficial Effects of Pulmonary Vasodilators on Pre-Capillary Pulmonary Hypertension in Patients with Chronic Kidney Disease on Hemodialysis - Keiji Kimuro; Kazuya Hosokawa; Kohtaro Abe; Kohei Masaki; Satomi Imakiire; Takafumi Sakamoto; Hiroyuki Tsutsui (Life, 2022)
Background: In patients with chronic kidney disease (CKD) on hemodialysis, comorbid pulmonary hypertension (PH) aggravates exercise tolerance and eventually worsens the prognosis. The treatment strategy for pre-capillary PH, including combined pre- and post-capillary PH (Cpc-PH), has not been established. Objectives: This study aimed to evaluate the impact of pulmonary vasodilators on exercise tolerance and pulmonary hemodynamics in patients with CKD on hemodialysis. Methods and Results: The medical records of 393 patients with suspected PH who underwent right heart catheterization were reviewed. Of these, seven patients had isolated pre-capillary PH and end-stage CKD on hemodialysis. Pulmonary vasodilators decreased pulmonary vascular resistance from 5.9 Wood units (interquartile range (IQR), 5.5–7.6) at baseline to 3.1 Wood units (IQR, 2.6–3.3) post-treatment (p = 0.02) as well as increased pulmonary capillary wedge pressure from 10 mmHg (IQR, 7–11) to 11 mmHg (IQR, 8–16) (p = 0.04). Pulmonary vasodilators increased the World Health Organization functional class I or II from 0% to 100% (p = 0.0002) and the 6 min walk distance from 273 m (IQR, 185–365) to 490 m (IQR, 470–550) (p = 0.03). Conclusions: Pulmonary vasodilators for PH in patients with CKD on hemodialysis decrease pulmonary vascular resistance and eventually improve exercise tolerance. Pulmonary vasodilators may help hemodialysis patients with pre-capillary PH, although careful management considering the risk of pulmonary edema is required.